Analysis of Floodwater Level and Periodic Maintenance of Celeng River, Bantul. Issue 1 (July 2021) - Ammara, N D; Maryono, A; Sulaiman, M
Abstract: Flooding in the Celeng River usually occurs after high-intensity rains. The Celeng River cannot accommodate any water from the hills around Imogiri and Dlingo. Channel modeling was carried out using HEC-RAS 5.0.7 simulations to determine the river capacity and floodwater level as a control design for periodic maintenance planning. The results of HEC-RAS 5.0.7 modeling in the existing conditions show that there were floods at several points. The usual effort is to make retaining walls. The river morphology, which is changed by the construction of the retaining wall, will accelerate the water rate so that the volume of water in the downstream part is high and will only move the flood to another place. This destructive to the environment, so flood mitigation using bio-engineering methods is proposed to answer the problem.